2021
DOI: 10.48550/arxiv.2105.08288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kuramoto model based analysis reveals oxytocin effects on brain network dynamics

Abstract: The oxytocin effects on large-scale brain networks such as Default Mode Network (DMN) and Frontoparietal Network (FPN) have been largely studied using fMRI data. However, those studies are mainly based on the statistical correlation or bayesian causality inference, lacking physical and neuroscience level interpretability. Here, we propose a Kuramoto model physical-based framework to investigate oxytocin effects on the phase dynamical neural coupling in DMN and FPN. Tested on fMRI data from 59 participants admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Accumulative evidence indicated that the OT influences human behavior (56) and brain activities (57)(58)(59). Since the previous behavioral results are mixed on whether OT sharpens or blurs self-other distinction (36,60,61), in the present study, participants make judgements in the self-other differentiation task with morphed faces.…”
Section: Discussionmentioning
confidence: 83%
“…Accumulative evidence indicated that the OT influences human behavior (56) and brain activities (57)(58)(59). Since the previous behavioral results are mixed on whether OT sharpens or blurs self-other distinction (36,60,61), in the present study, participants make judgements in the self-other differentiation task with morphed faces.…”
Section: Discussionmentioning
confidence: 83%